Radionuclide transit studies in the detection of oesophageal dysmotility. Issue 5 (May 1983) - Blackwell, J N; Hannan, W J; Adam, R D; Heading, R C
Abstract : A scintigraphic method is described to measure the transit of a fluid bolus through the oesophagus. Transit times in 16 normal subjects ranged from five to 15 seconds and were highly reproducible. Prolonged transit times were observed in 16 of 19 patients with known oesophageal motility disorders, and in these patients inspection of the time activity curves frequently permitted an adynamic oesophagus to be distinguished from one showing excessive incoordinate contractions. The technique was then applied prospectively to 50 patients referred for oesophageal motility studies and a comparison made between the oesophageal transit measurements and the findings on conventional oesophageal manometry. There was agreement between these tests in 42 (84%) of the 50 patients. The measurement of oesophageal transit may be made quickly and safely, without causing discomfort to the patient, and it appears to be at least as sensitive as manometry in the detection of oesophageal motility disorders.